Upcycling a condemned bus into an eco-hotel simulator for lodging management education in the Philippines - George Allen A. Primero; Joan Nebrida; Julie Anne B. Yaos; Rein Justine C. Balawid; Chrismarry Deanne P. Carino; Mark Anthony M. Jimena (Journal of Rural Tourism, 2026)
Purpose - This study examines the transformation of a condemned university bus into an eco-hotel simulator as an experiential learning tool for lodging management students at Nueva Vizcaya State University. Specifically, it aims to evaluate the simulator’s design features, sustainability components, and the practical challenges encountered in integrating sustainability-focused, hands-on learning within hospitality education.Design/Methodology/Approach - The study involved 67 respondents, comprising 60 lodging management students and 7 faculty members, who engaged directly with the eco-hotel bus simulator. Data were gathered through participant engagement and reflective inputs, and thematic analysis was employed to analyze perceptions related to functionality, visual appeal, space arrangement, sustainability features, and challenges associated with upcycling the condemned bus.Findings - The findings indicate that the simulator’s spatial arrangement, visual appeal, and functional areas effectively support experiential learning and the development of operational skills. Sustainability features, such as the use of recycled materials, energy-efficient systems, and eco-friendly design elements, were positively perceived and recognized as valuable for sustainability education. However, challenges related to limited space, ergonomic considerations, and the integration of sustainable features within a mobile structure were also identified.Originality/Value - This study highlights the potential of upcycled, simulation-based learning environments as innovative tools for enhancing practical competencies and sustainability awareness in hospitality education. The eco-hotel bus simulator presents a novel, cost-effective, and environmentally responsible approach that helps bridge the gap between theoretical instruction and real-world application.